Collaborative Governance dalam Pengelolaan Aset Desa Wisata Watu Rumpuk di Desa Mendak Kecamatan Dagangan Kabupaten Madiun - Indra Wiratma; Sri Wahyuni (Public Administration Dept, Faculty of Social and Political Science, 2022)
This study aims to determine the process of Collaborative Governance in Asset Management of Watu Rumpuk Tourism Village in Mendak Village, Dagangan District, Madiun Regency. Data collection techniques using interviews, observation, and documentation. Based on Collaborative Governance indicators. The results of the study indicate that collaboration occurs with several dimensions (1) Face To Face Dialogue, is a direct, face-to-face conversation carried out between the Tourism Office and the Village Government and Village Communities who work together regarding the management and development of Watu Rumpuk Tourism in Mendak Village, Madiun Regency. (2) Trust building (Building Trust), is a person's trust with one another in the management and development stage of Watu Rumpuk Tourism, it is necessary for leaders who are able to realize the importance of collaboration regarding government in order to build Watu Rumpuk Tourism management. (3) Commitment to process, is a strong commitment and advice between the Tourism Office and the Village Government in maintaining a developed tourist area to remain safe, comfortable and peaceful. (4) Shared understanding, is the sharing of understanding about experiences between the tourism office and the village government which can be described as a shared vision and mission, common goals, general objectivity, and the same ideology. In this Collaborative Governance research, there are the most important aspects that must be applied in Collaborative Governance research in the Management of Watu Rumpuk Tourism Village Assets in Mendak Village, Degangan District, Madiun Regency, in the focus of research here there are 4 main aspects, namely (1) Collaborative Governance (Cooperation), (2) Government, (3) Private, (4) Community. there are deficiencies in the Management of Village Assets in Mendak Village, so an understanding of commitment in the process is needed, and a common understanding in the management of Village Assets in Mendak Village.